Operation and safety analysis of space lithium-cooled fast nuclear reactor. (February 2022) - Jin, Zhao; Wang, Chenglong; Liu, Xiao; Dai, Zhiwen; Tian, Wenxi; Su, Guanghui; Qiu, Suizheng
Highlights: A transient analysis code SALS is developed for space nuclear power system with stirling engine. The operation characteristics of lithium-cooled reactor with solar heat flux model is simulated and analyzed. The heat sink loss accident and reactivity insertion accident are simulated. Abstract: As the power requirements for deep space exploration continue to increase, space nuclear power systems are imperative. In this paper, a set of models are established for the lithium-cooled space reactor combined with the Stirling engine. The space lithium-cooled reactor system is modeled, and the result of the steady-state is checked with the maximum relative error of 13.3%. Moreover, the characteristics under the unprotected reactivity insertion accident (URIA) and the unprotected loss of heat sink accident (LOHA) are obtained and analyzed. The results showed that: a) the solar heat flux cause the radiator temperature to fluctuate but has limited impact, b) under LOHA, the temperature of hot spot decreases rapidly from 1436 K to 1423 K, verifying the inherent safety of the system, c) under URIA, the hot spot temperature rises to 1546 K within 160 s. This work provides a solid basis for the design and analysis of space nuclear systems.